A Rare Case of BCL2-Positive Multiple Myeloma Complicated with Follicular Lymphoma - Tsutsumi, Yutaka; Ito, Shinich; Kobayashi, Mirei; Teshima, Takanori (Case Reports in Hematology, 2022)
A 68-year-old woman presented with follicular lymphoma complicated by IgG kappa-positive multiple myeloma. In this case, both follicular lymphoma and plasma cells were positive for BCL2 by immunostaining. T-cell association in the FL and MM was also analyzed in this case. Some CD3-positive T-cells were found around the plasma cells. These cells were mainly CD8-positive T-cells and not CD4-positive T-cells. These results suggest that CD4-positive T-cells were not associated with the proliferation of the plasma cells in this case. Although the FL that developed was initially positive for BCL2 protein, this does not indicate that plasma cells were derived from FL cells because of the eventual complication that occurred in this case. Furthermore, in this case, rituximab and bendamustine were effective for FL. They were not effective for MM, however, demonstrating that additional treatment options are necessary for the simultaneous treatment of BCL2-positive MM with FL.